CYLD - A potential Mediator of tissue-specific Melanoma Metastasis - Schott, Mandy; de Jel, Miriam Martha; Boßerhoff, Anja Katrin; Kuphal, Silke (2018)
EVALuna2:203600

Loss of CYLD accelerates melanoma development and progression in the Tg(Grm1) melanoma mouse model - de Jel, Miriam Martha; Schott, Mandy; Lamm, Susanne; Neuhuber, Winfried; Kuphal, Silke; Boßerhoff, Anja Katrin (Oncogenesis, 2019)
The deubiquitinase cylindromatosis (CYLD) is a well-known tumor suppressor, found to be down regulated in many cancer types including breast cancer, colon carcinoma and malignant melanoma. CYLD is suppressed in human melanoma cells by the transcriptional repressor SNAIL1 leading to an increase of their proliferative, invasive and migratory potential. To gain additional insights into the distinct function of this tumor suppressor gene a new mouse model Tg(Grm1)Cyld−/− was generated. Herewith, we demonstrate that Cyld-deficiency leads to earlier melanoma onset and accelerated tumor growth and metastasis in the GRM1 melanoma mouse model. First, RNA sequencing data revealed a potential role of CYLD in the regulation of genes involved in proliferation, migration and angiogenesis. Experiments using cell lines generated from both primary and metastatic melanoma tissue of Tg(Grm1) Cyld−/− and Tg(Grm1) Cyld+/+ mice confirmed that loss of CYLD enhances the proliferative and migratory potential, as well as the clonogenicity in vitro. Moreover, we could show that Cyld-knockout leads to increased vasculogenic mimicry and enhanced (lymph-) angiogenesis shown by tube formation assays, immunohistochemistry and mRNA expression analyses. In summary, our findings reveal new functional aspects of CYLD in the process of (lymph-) angiogenesis and demonstrate its importance in the early process of melanoma progression.
CRIS-Team Scopus Importer:2019-10-18

Loss of CYLD promotes melanoma progression - de Jel, Miriam Martha; Schiffner, S.; Kuphal, Silke; Boßerhoff, Anja Katrin (2016)
EVALuna2:4737

Selenium-binding protein 1 is down-regulated in malignant melanoma - Schott, Mandy; de Jel, Miriam Martha; Engelmann, Julia C.; Renner, Philipp; Geissler, Edward K.; Boßerhoff, Anja Katrin; Kuphal, Silke (Oncotarget, 2018)
Selenium-binding protein 1 (SELENBP1) expression is reduced in various epithelial cancer entities compared to corresponding normal tissue and has already been described as a tumor suppressor involved in the regulation of cell proliferation, senescence, migration and apoptosis. We identified SELENBP1 to be down-regulated in cutaneous melanoma, a malignant cancer of pigment-producing melanocytes in the skin, which leads to the assumption that SELENBP1 also functions as tumor suppressor in the skin, as shown by others e.g. for prostate or lung carcinoma. However, in vitro analyses indicate that SELENBP1 re-expression in human melanoma cell lines has no impact on cell proliferation, migration or tube formation of the tumor cells themselves when compared to control-transfected cells. Interestingly, supernatant taken from melanoma cell lines transfected with a SELENBP1 re-expression plasmid led to suppression of vessel formation of HMEC cells. Furthermore, SELENBP1 re-expression alters the sensitivity of melanoma cells for Vemurafenib treatment. The data also hint to a functional interaction of SELENBP1 with GPX1 (Glutathione peroxidase 1). Low SELENBP1 mRNA levels correlate inversely with GPX1 expression in melanoma. The re-expression of SELENBP1 combined with down-regulation of GPX1 expression led to reduction of the proliferation of melanoma cells. In summary, SELENBP1 influences the tumor microenvironment and SELENBP1 action is functionally influenced by GPX1.
EVALuna2:34070